Anal canal squamous carcinoma - Magalhães,Maricruz Nunes (2017)
ABSTRACT Background: Anal canal carcinoma is a rare neoplasm, representing 2% of the digestive tumors, and the most common is squamous cell carcinoma, with an increasing incidence. Objective: The study aims to elucidate the pathogenesis of an increasingly prevalent disease, as well as to update treatment and prognosis. Methods: A literature search in Pubmed database, including articles from 2005 to 2015 and cross-research articles with the initial research. Results: Several studies prove the role of HPV as a major risk factor in the development of squamous cell carcinoma of anal canal, as well as a greater prevalence of this neoplasia in HIV-positive people and in those who practice receptive anal intercourse. In the last two decades chemoradiotherapy remains the treatment of choice, and abdominoperineal resection is reserved for those cases of treatment failure or recurrence. Evidence advances in order to adapt the treatment to each patient, taking into account individual prognostic factors and biological tumor characteristics. Conclusions: Squamous cell carcinoma of the anal canal is a neoplasm associated with HPV; therefore, screening and vaccination programs of male individuals, by way of prevention, should be started. Many studies are needed in order to achieve development in the treatment as well as in the evaluation of the biological characteristics of the tumor.